THE LEGACY IN THE RUBAI GENRE - Nizamova Feruza Alimullaevna (Euro Asian Journal Publishing, 2025)
In the article Amir Khusrav Dekhlavi’s huge heritage in the ruba’i genre is tried to study briefly. The aim of the article is to study the ideological and artistic system of the poet's works, to identify the poet's skills in the ruba’i genre, and also to define the role of his writings in the history of Persian-Tajik literature through analyzing his ruba’is. It is a scientific fact that he has profoundly influenced the other poets’ works in the Islamic region who wrote in Persian and Turkic afterwards.
Keywords: Persian literature; sufizm; rubai; poetry